PEMAKAIAN ADDITIVE MICRO SILICA DALAM CAMPURAN BETON UNTUK MENINGKATKAN KUAT TEKAN BETON NORMAL - Herri Mahyar (Politeknik Negeri Lhokseumawe, 2013)
Micro silica types sikafume is one plus altemate materials (additive) than fly ash is often used to increase the compressive strength of concrete. Composition of the same material used on condition fas 0.5. Addition sikafume in concrete mixed with composition 0%, 5%, 10%, 15, and 20%. The Specimens used in this study is a concrete cylinder diameter of 15 cm and height 30 cm by 5 pieces for each sample. Compressive strength testing done at the time the specimen reaches the age of 3,7, 14, and 28 days. The result showed the maximum compressive strength of concrete at 28 days is 21 MPa without adding sikafume. Maximum compressive strength due to the use of additive type sikafume (15%) achieved at the age of 28 days with a concrete compressive strength of 34 MPa.